2012
DOI: 10.1007/s13191-012-0201-2
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Produced on the Residual Maxillary Alveolar Ridge by Different Impression Materials and Tray Design: An In Vivo Study

Abstract: Increased ridge resorption may occur due to inappropriate pressure applied during final impression making phase of complete denture fabrication. This study was done to evaluate the pressure applied on the residual ridge while making impressions with two tray designs (with and without spacer) using, zinc oxide eugenol and light body polyvinyl siloxane impression material. Five edentulous subjects were randomly selected. For each of the five subjects four maxillary final impressions were made and were labelled a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 9 publications
1
9
0
1
Order By: Relevance
“…When the tray design was kept constant, there were no significant differences in tissue displacement between the different impression materials used across all the measuring points, except the anterior and posterior parts of the flabby tissues at the 8‐mm sagittal sections bilaterally. This is similar to the results of Reddy et al's in vivo study, reporting that in maxillary edentulous patients the pressures recorded when impressions were made with ZOE paste and light‐body type of VPS were similar; however, the studies by Frank and Masri et al suggest that the impression material used contributed to differences in pressure when making maxillary edentulous impressions. These findings indicated that the viscosity of the impression material is directly related to the amount of pressure produced.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…When the tray design was kept constant, there were no significant differences in tissue displacement between the different impression materials used across all the measuring points, except the anterior and posterior parts of the flabby tissues at the 8‐mm sagittal sections bilaterally. This is similar to the results of Reddy et al's in vivo study, reporting that in maxillary edentulous patients the pressures recorded when impressions were made with ZOE paste and light‐body type of VPS were similar; however, the studies by Frank and Masri et al suggest that the impression material used contributed to differences in pressure when making maxillary edentulous impressions. These findings indicated that the viscosity of the impression material is directly related to the amount of pressure produced.…”
Section: Discussionsupporting
confidence: 87%
“…The null hypothesis was rejected, because displacement of the flabby tissue was significantly affected by the tray designs and impression materials. Previous studies evaluated the factors that control tissue displacement caused by the force exerted while making impressions indirectly by assessing the pressure generated when making an impression rather than directly by assessing the amount of tissue displacement . Moreover, these studies only evaluated the displacement of the normal denture‐bearing areas, and could not explain or contribute to the understanding of the displacement of flabby tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 O seu uso nestas moldeiras leva a uma redução da pressão exercida sobre as cristas alveolares. 27 Em relação à colocação de stops e orifícios de escape nas moldeiras individuais, a maioria das pós -graduações Ibéricas não realizava nenhum dos dois. Porém, em Portugal, 50% realizava orifícios de escape.…”
Section: Discussionunclassified
“…The tray design can be altered either with spacers or perforating impression trays, scraping impression trays, using open trays with the window technique, and using detachable trays. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Trays with additional spacers and holes or trays that open near the flabby ridge area reduce tissue displacement. 18 Open window trays yield the smallest magnitude of displacement.…”
Section: Introductionmentioning
confidence: 99%